The role of psycho-oncology in the treatment of cancer patients (Texas Journal of Medical Science, 2022)
As a result of external factors causing negative changes in the human psyche, emotional disturbances, stress, and a violation of the norm of health in general lead to psychosomatic disorders. In the study of somatic diseases today, it has been proven that the disease cannot be cured without taking into account mental factors. It is advisable to study the stages of psychological change in the course of the disease to determine the possibility of providing psychotherapeutic care to oncology patients. All diseases cause changes in the human psyche, but the internal psychological manifestations of oncological diseases are unique